2011
DOI: 10.1007/s00421-011-1830-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in salivary antimicrobial peptides, immunoglobulin A and cortisol after prolonged strenuous exercise

Abstract: The aim of the present study was to examine whether amount of oral antimicrobial components, human β-defensin-2 (HBD-2), cathelicidin (LL-37), and immunoglobulin A (IgA), might be affected by prolonged strenuous exercise. Ten young male volunteers either exercised on recumbent ergometer at 75% [Formula: see text] for 60 min (exercise session) or sat quietly (resting session). Saliva samples were obtained at 60-min intervals during sessions for measurements of saliva antimicrobial components (HBD-2, LL-37, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 53 publications
6
35
2
1
Order By: Relevance
“…These findings agree with our previous work and that of others, which have shown a postexercise increase in salivary AMPs, including lactoferrin (1,21), lysozyme (1,21), LL-37 (10,38), and HNP1-3 (10). The postexercise increase in concentration and secretion rate of AMPs could arise from the exercise-induced neutrophilia that occurs in mucosal secretions (31) potentially due to airway inflammation or damage to the airway epithelial cells.…”
Section: Discussionsupporting
confidence: 93%
“…These findings agree with our previous work and that of others, which have shown a postexercise increase in salivary AMPs, including lactoferrin (1,21), lysozyme (1,21), LL-37 (10,38), and HNP1-3 (10). The postexercise increase in concentration and secretion rate of AMPs could arise from the exercise-induced neutrophilia that occurs in mucosal secretions (31) potentially due to airway inflammation or damage to the airway epithelial cells.…”
Section: Discussionsupporting
confidence: 93%
“…We found that acute dynamic exercise increased the secretion and/or concentration of a wide range of sAMPs, from the small cationic peptides LL--37 and HNP1--3, to larger polypeptides and proteins such as lactoferrin, lysozyme and salivary SIgA. These findings are consistent with previous findings that a single bout of exercise enhances the concentration and secretion of a number of sAMPs (Allgrove et al 2008;Davison et al 2009;de Oliveira et al 2010;Gillum et al 2014;Usui et al 2011;Walsh et al 1999;West et al 2010), but this study shows that fitness status significantly impacts this response. The secretion and/or concentration of all measured sAMPs tended to increase with exercise at a greater magnitude in the highly fit compared to the less fit cyclists, with significant fitness effects being observed for α--amylase, HNP1--3, LL--37, lactoferrin, and salivary SIgA.…”
Section: Discussionsupporting
confidence: 91%
“…Davison et al (2009) found that the concentration and secretion rates of LL--37 and HNP1--3 were significantly greater following a single bout of prolonged exercise at an intensity corresponding to 55-65% of V" O2 max. Additional studies examining the relationship between exercise and sAMPs have yielded similar results, demonstrating significant increases in the concentration and/or secretion of total salivary protein, α--amylase, salivary SIgA, lactoferrin, lysozyme, human ß--defensin--2, and LL--37 following acute bouts of exercise (Allgrove et al 2008;de Oliveira et al 2010;Gillum et al 2014;Usui et al 2011;Walsh et al 1999;West et al 2010); however, this exercise--induced response appears to be dependent on exercise intensity and/or duration. While Allgrove et al (2008) showed significant increases in α--amylase and lysozyme secretion following 22 minutes of exercise at 75% VO2max and after an incremental effort test to exhaustion, no change in these sAMPS was found after 22 minutes of exercise at 50% VO2max.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Continuous intensive training reduces SIgA levels and increases the risk of URTI in athletes (Nieman 1994), whereas continuous moderate exercise training increases SIgA levels and reduces the risk of infections (Akimoto et al 2003;Klentrou et al 2002;Shimizu et al 2007). Intense exercise reduces SIgA secretion (Tomasi et al 1982;Mackinnon and Jenkins 1993), and the reduction of SIgA levels is sustained for 2 h after exercise (Usui et al 2011).…”
Section: Introductionmentioning
confidence: 96%